The personal and the private in the piety of the biblical psalmist - Berković, Danijel, teolog (Array, 2020)
The work discusses a correlative relationship between the notions of the personal and the private in the context of biblical psalmist’s piety. Elements of anthropology (heart, soul, face) will obtain considerable importance, particularly the ideas of face and soul (פנה and נפש). These will be corresponding to the Greek idea of προσοπων (prosopon), person. The authors will insist on the distinction between the ideas of personal and private, but they will also recognize the interdependence of these ideas, in recognition that the individual and the societal, are both contributions in the building of the subject as the self. In Paul’s Hymn to Love (1 Cor. 13) the complementary nature between the personal and the private is evident. There we find both passive and active subject’s role claiming this double aspect of the human subject - personal and private. Discussion in this work follows long-term debates over the nature of the subject, its personality, and its privacy.